The Blows and Capoeira Movements From the Caricatures of Calixto Cordeiro - Araújo, Paulo Coêlho; Jaqueira, Ana Rosa (Frontiers in Psychology, 2020)
This study examines some elements of a historical and social nature of Capoeira, from the caricatures produced by Calixto Cordeiro, which illustrated the work of Lima Campos in 1906. The work based on a documentary and bibliographic analysis in order to interpret the data reported by Cordeiro, comparing them with other descriptions of various kinds about Capoeira presented by illustrious literates. The results of these analyses revealed substantial information about strikes / movements of this fight, as well as their different denominations, slangs and expressive forms, often associated with different groups of practitioners in different Brazilian cities.